Complete Question:
The output equals 1 less than three times the input
Write and solve any equation to find input when the output is -3
Answer:
y = 3x - 1
x = -⅔ when y = -3
Step-by-step explanation:
Given
Represent the input with x and the output with y.
First, we need to write out the output as a function of the input.
[Three times the input] implies 3 * x
[1 less than this] implies 3*x - 1
The above expression is said to be the output.
So,
y = 3 * x - 1
y = 3x - 1
The next part of the question is to solve for x when y = -3
Substitute -3 for y in y = 3x - 1
-3 = 3x - 1
Collect Like Terms
3x = 1 - 3
3x = -2
Solve for x
x = -⅔